2013
DOI: 10.1371/journal.pone.0074996
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phosphate as a Risk Factor for Cardiovascular Events in People with and without Chronic Kidney Disease: A Large Community Based Cohort Study

Abstract: BackgroundSerum phosphate is a known risk factor for cardiovascular events and mortality in people with chronic kidney disease (CKD), however data on the association of these outcomes with serum phosphate in the general population are scarce. We investigate this relationship in people with and without CKD in a large community-based population.MethodsThree groups from an adult cohort of the Quality Improvement in Chronic Kidney Disease (QICKD) cluster randomised trial (ISRCTN56023731) were followed over a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 42 publications
(41 reference statements)
2
104
0
2
Order By: Relevance
“…The abnormality is significantly associated with increased mortality among ESRD patients on hemodialysis [5][6][7]. Studies have also shown a strong association of hyperphosphatemia with cardiovascular morbidity and mortality in ESRD patients [8][9][10]. Consequently, adequate control of serum phosphate is a critical component in the clinical management of ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormality is significantly associated with increased mortality among ESRD patients on hemodialysis [5][6][7]. Studies have also shown a strong association of hyperphosphatemia with cardiovascular morbidity and mortality in ESRD patients [8][9][10]. Consequently, adequate control of serum phosphate is a critical component in the clinical management of ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…12,18 However, reports investigating the association of serum phosphorus level with cardiovascular outcome or mortality have shown variable results in individuals with normal kidney function. 16,[19][20][21][22][23][24][25] A possible explanation for this variability is the different distribution of serum phosphorus levels according to age, 26 sex, 20,26,27 hormonal status, 27,28 circadian variation, 29,30 and dietary phosphorus intake. Although a recent study regarding the interaction of dietary intake and diurnal variation demonstrated that fasting serum phosphorus levels are associated with all-cause mortality, 31 the study population included individuals with and without kidney disease.…”
mentioning
confidence: 99%
“…The association is even observed in early-stage CKD and is independent of other traditional CV risk factors. 5, 6 Along with other factors, hyperphosphatemia is involved in the development of vascular calcification (VC) and endothelial dysfunction (ED), 7-9 both of which are major nontraditional CV risk factors for CKD. Phosphate is able to act either directly on these parameters or indirectly via the FGF23/Klotho and PTH axes (Figure 1).…”
mentioning
confidence: 99%